2010
DOI: 10.1111/j.1365-2524.2010.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Physically demanding workloads and the risks of musculoskeletal disorders in homecare workers in the USA

Abstract: Although musculoskeletal disorders (MSDs) are prevalent among homecare workers, little is known about the MSD risk factors. This study investigated whether physically demanding workloads among homecare workers are related to MSDs, especially in neck, shoulder and back pain. Data were taken from two waves of a random sample (June to December 2003 and December 2003 to February 2004). The sample included 1643 homecare workers at Wave 1 and 1198 homecare workers at Wave 2, respectively. A basic telephone interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…However, the use of relatives as paid providers may bring up unintended complications regarding the actual delivery of care, because of the well-documented risk of occupational injury and musculoskeletal disorders (MSDs) among PAS providers [7,8] . Musculoskeletal disorders (MSDs) are defined as "injuries or disorders of the muscles, nerves, tendons, joints, cartilage, and disorders of the nerves, tendons, muscles and supporting structures of the upper and lower limbs, neck, and lower back that are caused, precipitated or exacerbated by sudden exertion or prolonged exposure to physical factors such as repetition, force, vibration, or awkward posture" [9] .…”
Section: Issn 2324-7940 E-issn 2324-7959mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of relatives as paid providers may bring up unintended complications regarding the actual delivery of care, because of the well-documented risk of occupational injury and musculoskeletal disorders (MSDs) among PAS providers [7,8] . Musculoskeletal disorders (MSDs) are defined as "injuries or disorders of the muscles, nerves, tendons, joints, cartilage, and disorders of the nerves, tendons, muscles and supporting structures of the upper and lower limbs, neck, and lower back that are caused, precipitated or exacerbated by sudden exertion or prolonged exposure to physical factors such as repetition, force, vibration, or awkward posture" [9] .…”
Section: Issn 2324-7940 E-issn 2324-7959mentioning
confidence: 99%
“…In the United States, the rate of MSDs among PAS workers exceeded that among construction, mining and manufacturing workers [14] . Recently, Kim et al [7] investigated this MSD risk prospectively, using a random sample of over 1600 paid providers. Study results indicated that providers' physical demands providing care are a significant risk factor for MSDs.…”
Section: Issn 2324-7940 E-issn 2324-7959mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that a combination of tasks that require bending may increase the risk of musculoskeletal problems for PAS providers. Similarly, Kim and colleagues found a modest increase in risk (OR=1.14; CI=1.08-1.19) for physical demands among PAS providers (Kim et al, 2010). Other studies of care providers have also found challenges in identifying the role of physical risk factors in WRMSDs or related disability (Ando et al, 2000;Simon et al, 2008), or determining the most problematic physical risk factor in home care (Cheung et al, 2006;Ono et al, 1995).…”
Section: Temporal Factorsmentioning
confidence: 97%
“…With upwards of 44% of low back pain patients in the general working population reporting a recurrence within one year (Woolf & Pfleger, 2003), multiple episodes or chronicity among home care providers also needs to be considered. Although several studies have documented rates among home health nurses and aides, only a few have focused on paid PAS workers in the home (Kim et al, 2010;Meyer & Muntaner, 1999;Ono et al, 1995).…”
Section: Introductionmentioning
confidence: 99%